PERTUMBUHAN DAN HASIL BLEWAH (Cucumis melo var. cantalupensis L.) PADA TINGKAT PENJARANGAN BUAH DAN DOSIS PUPUK NPK BERBEDA - Lusiana Septiriyani; Mohammad Chozin; Yulian Yulian (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2021)
[PRODUCTIVITY AND FRUIT QUALITY OF CANTALOUPE AT DIFFERENT RATES OF FRUIT THINNING AND NPK FERTILIZER APPLICATION]. Productivity and fruit quality of cantaloupe depend on the availability of nutrients and the number of fruits maintained. The aim of this study was to compare the productivity and fruit quality of cantaloupe at different rates of fruit thinning and NPK fertilizer application. The research was conducted in August-October 2020 on street Kapuas V, Lingkar Barat Village, Gading Cempaka District, Bengkulu city. A field experiment was arranged in a randomized complete block design (RCBD) with 3 replications for alloting two factorial treatments structure, namely rates of fruit thinning (no fruit thinning, thinned to one fruit /plant, thinned to two fruits/plant, and thinned to three fruits/plant) and rates of NPK fertilizer application (400, 600, and 800 kg/ha) on rhe experimental plots. The results showed that fruit thinnings resulted no increament in crop productivity, but the fruit quality was improved as fewer number of fruits were retained on each plant. The NPK fertilizer at 400, 600, and 800 kg/ha were not able to increase the productivity of cantaloupe  and the quality of the  produced fruit when  the application were made only at planting and 23 days after planting.